Pengaruh Kesiapan Belajar dan Motivasi Belajar terhadap Hasil Belajar pada Mata Pelajaran IPS Siswa Kelas VIII di SMP Negeri 1 Tarumajaya Bekasi - Oyin Supriyatna; Adeng Hudaya; Abdul Munir (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
The purpose of this study was to determine the effect of learning readiness and learning motivation together on the learning outcomes of social studies subjects for class VIII students at SMPN 1 Tarumajaya Bekasi. In addition, researchers hope that readers, especially schools, can pay attention to student learning readiness and student motivation to improve learning outcomes. The method used in analyzing this research is a quantitative research method. The population in this study was 400 of all class VIII students for the 2020/2021 academic year and a sample of 92 students. Through correlation calculations obtained rx1y 0.740 and rx2y 0.748, which means there is a high correlation between X1 to Y and X2 to Y. Analysis of the coefficient of determination obtained 0.900 This shows that the contribution of variables X1 (Readiness to Learn) and X2 (Learning Motivation) to variable Y (Results learning) by 90% and the remaining 10% is determined by other factors not examined in this study. The multiple linear regression coefficient shows the constant value a = 11.726 b1 = 0.417 and b2 = 0.445. Testing the statistical hypothesis obtained by the results obtained F arithmetic > F table (401.052 > 3.100) shows that simultaneously Learning Readiness and Learning Motivation together affect Learning Outcomes. While the variable t test X1 t count = 16.106 > t table = 1.990. Shows that there is an effect of learning readiness on the learning outcomes of class VIII students at SMPN 1 Tarumajaya Bekasi. And the t-test of the X2 variable tcount = 17.617 > ttable = 1.990. Shows that there is an influence of learning motivation on the learning outcomes of class VIII students at SMPN 1 Tarumajaya Bekasi